Analisis Minat Terhadap Generasi Z Dalam Pembelian Produk Asuransi Syariah - Jumriani Siregar; Siska Permata Sari Harahap; Thasya Virdinia; Nurhayati Harahap (CV. Ulil Albab Corp, 2024)
This article aims to analyze the interest of Generation Z in purchasing Sharia-compliant insurance products. The objectives of this research are to understand the factors influencing Generation Z's interest in buying Sharia-compliant insurance products and to evaluate their preferences and motivations regarding these products. The research method involves surveys and data analysis of a sample of Generation Z individuals involved in the purchase of Sharia-compliant insurance. The results reveal that factors such as Islamic values, trust in the Sharia financial system, and the need for protection are primary drivers of Generation Z's interest in choosing Sharia-compliant insurance products. The conclusions drawn from this analysis provide crucial insights for the insurance industry to adapt marketing strategies that align with the preferences and needs of the younger generation in the context of Sharia-compliant financial products.